Cultural Interaction Program in Corporate Social Responsibility (CSR) PT. Pertamina : Netnography Study - Akma, Hidayatul; Sokarina, Ayudia (East Asian Journal of Multidisciplinary Research, 2024)
The aim of this research is to understand cultural interactions in Pertamina's Corporate Social Responsibility (CSR) program. This research uses an interpretive perspective and netnography as research methodology. Data collection uses a passive approach through multiple online platforms, namely Instagram, TikTok and Facebook. The data that has been collected is then analyzed using coding, noting and abstracting. The research results show that Pertamina's CSR program generates various responses and interactions among the community. First, the view 'without money you are nothing". Second, accounting treatment. Third, scarcity. Fourth, the concept of trade monopoly. Fifth, be careful (tabayun). Sixth, having bad prejudice (suudzon). Seventh, swearing. Lastly, positive comments in the form of: appreciation, support and hope. By involving the community in the decision process and design of CSR programs, this research can contribute to the empowerment of society as a whole. The implication is to create a more balanced relationship between companies and society, where society feels they have a stake in positive change.